If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying m = (2 + -1) Combine like terms: 2 + -1 = 1 m = (1) m = 1 Solving m = 1 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Simplifying m = 1
| w=4+15 | | 2(x-2)=2x-6 | | 2x-8x+4=x-9+13 | | 3x-14=3x-14 | | 1.1x+8=0.5x+20 | | 1.1x+8=0.5x+29 | | (20-2x)x=90 | | 5227.50=5100(1+.025r) | | y=9.5+100 | | y=-0.62+0.0005x | | y=-0.62+0.0005211x | | y=0.0005211x+-0.62 | | 2c+4+3c=-16 | | 2x^2+1=2x+12 | | 4y-5x=40 | | .6x+1.9x=5 | | .6x+1.9=5 | | 2x^2+43x-2730=0 | | a+5=3 | | 7-6(3-8x)=0 | | x^2-14x+36= | | log(100)=10 | | ?10x+1+7x=37 | | ?10x+1+7x=32 | | ?10x+1+7x= | | ?10x+1+7x=37 | | log(x+5)-log(1-5x)=0 | | .50(x-6)+1=2(x-10)-3 | | 6x+4+8x+18+(180-20x+4)=180 | | 10y-x= | | 3w-10=50 | | log(x+5)=log(1-5x) |